Microstructure and mechanical properties in friction stir welded 5A06 aluminum alloy thick plate. (5th January 2017) - Guo, Ning; Fu, Yunlong; Wang, Yuzhong; Meng, Qiang; Zhu, Yuxiao
Abstract: Friction stir double-sided butt welding was carried out for the joining of 5A06 aluminum alloys with thickness of 108 mm, and sound welds with full penetration were produced. Microstructure characterizations of the welding joint were investigated by optical microscopy, electron back-scattered diffraction and transmission electron microscopy (TEM). The results indicate that void defects are observed in shoulder-affected zone (SAZ) and grain size of equiaxed grains in SAZ and weld nugget zone (WNZ) decreases gradually along the thickness direction, while in SAZ the dislocation density is significantly lower and the sub-grain size is much larger than those in WNZ. Microhardness surveys reveal that on the upper part of the joint hardness profile presents a "V" shape and minimum hardness appears in SAZ whereas that in other regions exhibits a "W" shape and the lowest hardness value occurs in the heat-affected zone adjacent to the advancing side. The investigation of tensile properties on the FSW joint indicates the WNZ exhibited superior tensile properties compared with SAZ, and the analysis of fracture surface using the scanning electron microscopy (SEM) demonstrates that fractures in all tensile specimens are ductile fracture due to the presence of dimples with different sizes. Graphical abstract: Highlights: 5A06 aluminium alloy rolled plates with thickness of 108 mm was welded successfully adopting friction stir double-sided butt welding In shoulder-affected zone and weld nugget zone, grain size decreases and dislocation density increases along the thickness direction In shoulder-affected zone, microstructure distribution is inhomogeneous and strain strengthening effect of the base metal weakens obviously On welding joint upper part, microhardness profile presents "V" shape whereas that in other regions exhibits "W" shape All tensile specimens sliced from welding joint are ductile fracture and mechanical properties on upper area is worst